Factors that Influencing Sputum Conversion at the End of Intensive Phase on TB-DM Patients at Medical Health Service in Medan - Pertiwi, Vani Gita; Sinaga, Bintang YM; Lindarto, Dharma (Universitas Muhammadiyah Sumatera Utara, 2021)
Tuberculosis and type 2 DM are the main problems of health in the world, including Indonesia. Many sputum conversion failures are found in TB-DM patients. This study aims to know about the factors that influence sputum conversion at the end of the intensive phase on TB-DM patients at the Medical Health Service in Medan. This research was carried out in a Specialized Lung Hospital and eight Health Centers in Medan. The Design of this study is observational analytic with a Cross-Sectional approach that took place in October-December 2019. Of 76 patients, there were 65 subjects (85.5%) with sputum conversion and 11 subjects (14.5%) without sputum conversion, the number of male patients was 48 subjects (63.2%), elderly were 51 subjects (67.1%), the normals BMI were 54 subjects (71.0%), patients with smoking were 4 subjects (5.3%), previous alcohol consumptions were 6 subjects (7.9%), current blood sugar levels 200 mg/dl are 23 subjects (30.2%) and the patients which using the anti-diabetes medication regularly were 62 subjects (81.6%). This study found that there was a significant relationship between alcohol, current blood sugar levels, and regularity using anti-diabetes medication with sputum conversion (p=0.036, p=0.001, p=0.001), while the factors that influence sputum conversion are alcohol and regularity using anti-diabetes medication (p=0.032, dan p=0.001).